Errors of Analysis in Distance Assessment: Effects of Vertical on Horizontal Components. (May 2020) - Dopkins, Stephen
(a) Participants indicated, for pairs of circles whose locations varied on the horizontal and vertical axes of a frontal plane, whether the horizontal distance between the circles exceeded a target horizontal distance. The error rate depended on the vertical as well as the horizontal distance between the circles. (b) Participants indicated, for pairs of circles that were varying horizontal (or vertical) distances and a constant vertical (or horizontal) distance apart in a frontal plane, whether the horizontal (or vertical) distance between them matched a target horizontal (or vertical) distance. Incorrect "match" responses were more likely if the horizontal (or vertical) distance between the circles was less than as opposed to greater than the target distance. The results suggest that distance judgments for pairs of stimuli varying on the horizontal and vertical axes are based on the overall distance between the stimuli, with the relevant axis given more weight than the irrelevant axis in assessment of the distance. The results do not support the view that that such distance judgments are based on the relevant distance between the stimuli, with the relevant and irrelevant axes being erroneously interchanged on some iterations of the assessment process.